Tennis at the elite level - An ITF technical centre review - Capel-Davies, J. (Coaching and Sport Science Review, 2017)
In order to fulfil its mission, the Technical Centre strives to quantify the parameters that describe the current nature of tennis at the elite level, and thus constitute `the state of the game`. The Technical Centre`s annual review of the state of the game consists of player analysis, including match statistics, and monitoring the equipment used by players.